Boosting students' achievement in economics in senior secondary schools in Ibadan, Oyo State: the role of teachers' job satisfaction (2023)
This study examined the influence of teachers 'job satisfaction on students' achievement in Economics in Ibadan, Oyo state. The design adopted was the survey research design. The population of this study comprised all Economics teachers and all senior secondary two (SSII) students offering Economics in Ibadan, Oyo state. The sample for the study consisted of 30teachers and 600 students from the selected senior secondary schools. Two instruments used for data collection were Teachers' job satisfaction questionnaire (r=) and Economics Achievement Test (r=). Inferential statistics was used to analyse data for the study with the aid of Statistical Package for Social Sciences 23 (SPSS). Data were analysed using. Findings revealed that teachers' job satisfaction (working conditions, recognition, and compensation) had a significant positive significant contribution (R2 = 267, F(2.27) = 9.01) to students' achievement in Economics in Ibadan, Oyo state. The results also indicated that working conditions (β = 0.85), recognition (β = 0.12), and compensation (β = 0.10) relatively contributed to students' achievement in Economics. Based on the findings, it was concluded that all three dimensions of teachers' job satisfaction considered in this study are factors that influenced students' achievement in Economics in senior secondary school in Ibadan, Oyo state. The study, therefore, recommended that for improved performance of students in Economics, efforts should be made by stakeholders to improve on teachers' job satisfaction.